Coronavirus fake news in Russia: specificity and criteria for detection - Demushina, Olga; Semikina, Yulia (Rizoma, 2020)
The paper examines special features of fake news about COVID-19 published in Russian social media. Based on the literature review and the analysis of fake news stories circulating in Russian social media and related to COVID-19, the criteria for fake news detection were developed: aim, wide circulation online, public interest, aggressive techniques of dissemination, outrageous nature, falsity, intentionality, low quality, simple ways of problems decision, encouraging readers to share the article, “screaming” headlines.